2020
DOI: 10.1101/2020.02.18.953596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific Inhibition of GSK-3β by Tideglusib: Potential Therapeutic Target for Neuroblastoma Cancer Stem Cells

Abstract: Neuroblastoma is an embryonic tumor that represents the most common extracranial solid tumor in children. Resistance to therapy is attributed, in part, to the persistence of a subpopulation of slowly dividing cancer stem cells (CSCs) within those tumors. Glycogen synthase kinase (GSK)-3β is an active proline-directed serine/threonine kinase, well-known to be involved in different signaling pathways entangled in the pathophysiology of neuroblastoma. This study aims to assess the potency of an irreversible GSK-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…cell types. Previous reports demonstrated that Tideglusib impaired the proliferation and migration of human neuroblastoma cell lines (Bahmad et al, 2020(Bahmad et al, , 2021 and human osteosarcoma cell lines (Wei et al, 2021). Thus, it can be speculated that the effect of Wnt on cell proliferation is cell type specific.…”
Section: Discussionmentioning
confidence: 98%
“…cell types. Previous reports demonstrated that Tideglusib impaired the proliferation and migration of human neuroblastoma cell lines (Bahmad et al, 2020(Bahmad et al, , 2021 and human osteosarcoma cell lines (Wei et al, 2021). Thus, it can be speculated that the effect of Wnt on cell proliferation is cell type specific.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies of the involvement of the GSK-3 in many diseases pathways leading to emerge it in the The Anticipated Effect of Glycogen Synthase Kinase 3 (GSK3) Antagonist on Pulp Tissue Repair (627) pharmacological chemistry research field as a very interesting therapeutic target for the development of selective inhibitors as potential new drugs (24,(26)(27)(28)(29) . So glycogen synthase kinases 3 (GSK3) inhibitors drug have been developed.…”
Section: Introductionmentioning
confidence: 99%